Bleeding profile of women using a drospirenone-only pill 4 mg over nine cycles in comparison with desogestrel 0.075 mg - Palacios, S. (PLoS One, 2020)
BACKGROUND: Progestin-only pills are associated with irregular bleeding pattern including amenorrhea. Desogestrel 75mcg even being a pill that inhibits ovulation shows a poor cycle control that limits a more common use. A drospirenone (DRSP)-only pill was developed to improve the bleeding profile. METHODS: A phase III study in healthy women aged 18 to 45 years was performed to compare the bleeding profile and safety of women taking a DRSP only pill in a regime of 24 days of 4 mg of DRSP tablets followed by 4 days of placebo versus desogestrel 0.075 mg per day continuously over 9 cycles. A total of 858 women with 6691 drospirenone and 332 women with 2487 desogestrel treatment cycles were analyzed. The primary endpoint was the proportion of women with bleeding/spotting days in each cycle from cycles 2 to 9 and cumulative in cycles 2 to 4 and cycles 7 to 9 including and excluding those with amenorrhea. FINDINGS: In each cycle, up to cycle 7, the proportion of women with unscheduled bleeding including those which did not bleed was statistically significantly lower in the DRSP group than in the DSG group (p = 0.0001, chi-square test). The mean [SD] number of unscheduled bleeding and spotting days during cycles 2–9 was statistically significantly lower in the DRSP group than in the DSG group (21.5 [22.86] days vs. 34.7 [33.73] days, p = 0.0003, Wilcoxon-rank-sum-test). Excluding amenorrhoeic women following results were obtained: In the cycles 2–6, the proportion of women with unscheduled bleeding was statistically significantly lower in the DRSP group than in the DSG group (p = 0.0001, chi-square test). The mean [SD] number of bleeding days was 8.6 [8.52] days vs. 12.9 [16.47] days, p = 0.0233. CONCLUSIONS: This report describes the improvement in bleeding profile of women using the new DRSP only oral contraceptive in comparison to DSG providing a better quality of live and adherence to the contraceptive method. EudraCT registration number: 2011-002396-42.